Explanations and Representations of Violence by School-age Brazilian Youths - Fernandez Villanueva, Concepcion; Revilla Castro, Juan; Dominguez Bilbao, Roberto; Salles, Leila Ferreira [UNESP]; Silva, Joyce Paula [UNESP] (Ministry Education & Science, 2013)
The violence staged by young people has often been subjected to scientific analysis. The way youths speak, in their role as aggressors or as victims, is examined to determine how they experience violence in a number of different spheres. Repeated group interviews are used to analyze how violence is explained and depicted within the family, at school and in the neighbourhood by two groups of young people (14-17 years old) attending the same school on the outskirts of Rio Claro, Sao Paulo, Brazil. One of the groups involved is identified by the school as violent, and the other, as non-violent. Discourse analysis leads to two conclusions. First, the different contexts of violence infuse a mistrust of institutions, the environment and personal relationships into the subjects' experience, forming a fabric that clouds future prospects. Second, the group of youths identified as violent have a more simplistic, pessimistic view of reality: They see the world in black and white, and they lay no stock in the possibility that violence can be avoided. Consequently, they use violence and understand violence as a defensive strategy that gives one identity. On the other hand, the group identified as nonviolent feels it possible to intervene in situations with nonviolent tools like words. For the young subjects, violence is a context that they assume; it cancels their ability to identify rules and institutions, but it does not generate an effective interaction strategy. Violence causes their social microcontext (in which action prevails over meaning or meaning equals action) to assume overblown dimensions. Any intervention strategy must take into account this indissoluble unity between meaning and action.
Keywords: School violence; youth; qualitative methods; group interview; Brazil